2020
DOI: 10.1017/mor.2019.50
|View full text |Cite
|
Sign up to set email alerts
|

Deterrence Effects: The Role of Authoritarian Leadership in Controlling Employee Workplace Deviance

Abstract: Drawing upon two independent samples from mainland China, we propose and investigate the deterrence function of leadership behavior focused on control. We suggest that controlling leadership, specifically, authoritarian leadership, deters employees’ deviance under certain conditions. That is, authoritarian leadership thwarts employees’ interpersonal deviance behavior when leaders send clear signals of potential punishments of non-compliance by showing low leader benevolence, and when employees are highly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 89 publications
(128 reference statements)
0
32
0
1
Order By: Relevance
“…Specifically, supervisors mainly take the following steps to prevent the negative behavior of employees in the workplace: (1) creating an organizational moral atmosphere, because the type and intensity of organizational moral atmosphere will affect employee workplace deviance behavior; (2) providing objectives and methods for employees, establishing trust relations within the organization through reasonable guidance and management by objectives, and establishing a constructive role in the organizational culture; and (3) aligning rewards and punishments to real performance [ 44 , 45 ]. Leadership plays an important role in the implementation of reward and punishment, and workplace deviance behavior is closely affected by a reward and punishment system [ 46 ]. Furthermore, the extant literature suggests that there is a positive correlation between transformational leadership and leadership effectiveness [ 47 ], while transactional leadership pays more attention to criticism, correction, and punishment of workplace deviance behavior.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Specifically, supervisors mainly take the following steps to prevent the negative behavior of employees in the workplace: (1) creating an organizational moral atmosphere, because the type and intensity of organizational moral atmosphere will affect employee workplace deviance behavior; (2) providing objectives and methods for employees, establishing trust relations within the organization through reasonable guidance and management by objectives, and establishing a constructive role in the organizational culture; and (3) aligning rewards and punishments to real performance [ 44 , 45 ]. Leadership plays an important role in the implementation of reward and punishment, and workplace deviance behavior is closely affected by a reward and punishment system [ 46 ]. Furthermore, the extant literature suggests that there is a positive correlation between transformational leadership and leadership effectiveness [ 47 ], while transactional leadership pays more attention to criticism, correction, and punishment of workplace deviance behavior.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Employees may exhibit deviant behavior, defined as undesirable and expensive forms of voluntary employee behavior that violates significant organizational norms and threatens organizational well-being (Robinson and Bennett, 1995, p. 556), toward their organization with disconcerting frequency (Bennett and Robinson, 2000). Given the critical role of leadership, extensive literature has examined the effects of various leadership styles on organizational deviance, such as abusive leadership (Mitchell and Ambrose, 2007), authoritarian leadership (Zheng et al , 2020), charismatic leadership (Brown and Trevino, 2006), ethical leadership (Mayer et al , 2009) and servant leadership (Paesen et al , 2019). The findings of these studies indicate that team leaders can shape employees' values and perceptions of justice, which in turn influence employees' deviance.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have primarily focused on its detrimental outcomes (Li et al, 2021;Ludeke et al, 2013), such as poor performance (Li et al, 2021;Wang et al, 2018a, b) and job dissatisfaction (Wang et al, 2018a(Wang et al, , b, 2020. However, as Zheng et al (2020) observed, the current research on authoritarian leadership has drawn an overly simplistic conclusion, and authoritarian leadership may be positively associated with employee outcomes. Zheng et al (2020) found that authoritarian leadership can thwart employees' interpersonal deviance behavior.…”
Section: Introductionmentioning
confidence: 81%
“…Relating to the prevalence of authoritarian leadership, there is a huge debate in the literature on the effectiveness of authoritarian leadership (Harms et al, 2018;Zheng et al, 2020). Researchers have primarily focused on its detrimental outcomes (Li et al, 2021;Ludeke et al, 2013), such as poor performance (Li et al, 2021;Wang et al, 2018a, b) and job dissatisfaction (Wang et al, 2018a(Wang et al, , b, 2020.…”
Section: Introductionmentioning
confidence: 99%